2006
DOI: 10.1021/ja058096q
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Catalyzed Asymmetric Alkylation of Secondary Phosphines:  Enantioselective Synthesis of P-Stereogenic Phosphines

Abstract: The chiral Pt catalyst precursor Pt((R,R)-Me-Duphos)(Ph)(Cl) mediated alkylation of racemic secondary phosphines PHR(R') with benzyl halides in the presence of base to give enantioenriched tertiary phosphines PR(R')(CH2Ar). Similar reactions of bis(secondary) phosphines yielded chiral diphosphines in up to 93% ee and with good rac/meso diastereoselection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(74 citation statements)
references
References 22 publications
1
72
0
1
Order By: Relevance
“…Scriban and Glueck recently reported a platinum-catalyzed asymmetric phosphination of 2,6-bis(bromomethyl)pyridine with PHMeIs (Is = 2,4,6-tris(isopropyl)phenyl) to generate the corresponding P-stereogenic diphosphine 12M eIs in up to 72 % ee. [35] To date, no application of these chiral PNP derivatives to coordination chemistry or stoichiometric/catalytic reactivity studies has been reported.…”
Section: Phmentioning
confidence: 99%
“…Scriban and Glueck recently reported a platinum-catalyzed asymmetric phosphination of 2,6-bis(bromomethyl)pyridine with PHMeIs (Is = 2,4,6-tris(isopropyl)phenyl) to generate the corresponding P-stereogenic diphosphine 12M eIs in up to 72 % ee. [35] To date, no application of these chiral PNP derivatives to coordination chemistry or stoichiometric/catalytic reactivity studies has been reported.…”
Section: Phmentioning
confidence: 99%
“…The origin of enantioselectivity, as in the Pd-catalyzed asymmetric cross-couplings described above, is the interconversion of diastereomeric phosphido complexes, whose speciation and relative rates of nucleophilic attack determine the product ratio. In the case of Pt ((R,R)-Me-DuPhos)(Ph)(PMeIs), as with the Pd analog in Scheme 43 above, the major product phosphine was formed from the major diastereomeric phosphido complex (Scheme 63) [112][113]. Pt-catalyzed alkylations of bis(secondary) phosphines were diastereo-and enantioselective, yielding enriched mixtures of C 2 -symmetric rac and meso bis(tertiary) phosphines.…”
Section: Alkyl Halidesmentioning
confidence: 99%
“…Catalytic symmetric synthesis of P-stereogenic phosphines by cross-coupling of secondary phosphines with benzyl or other alkyl halides was promoted by chiral Pt and Ru complexes [112][113][114]. The key step is believed to be the nucleophilic attack of a metal-phosphido complex on a free electrophile; the background reaction of the unactivated nucleophilic substrate is much slower.…”
Section: Alkyl Halidesmentioning
confidence: 99%
“…Scriban und Glueck berichteten kürzlich über eine Platin-katalysierte asymmetrische Phosphanierung von 2,6-Bis(brommethyl)pyridin mit PHMeIs (Is = 2,4,6-Triisopropylphenyl) zur Herstellung des P-stereogenen Diphosphans 12 MeIs mit Enantiomerenüberschüssen bis 72 % ee. [35] Studien zur Koordinationschemie dieser chiralen PNP-Derivate oder zu ihrer Anwendung in stöchiometri-schen oder katalytischen Reaktionen stehen noch aus.…”
Section: Einführungunclassified